Effect of Plasma Medium in Electromagnetic Wave - Ja’afar, H.; Abdullah, R.; N.Dagang, A.; Sadeghikia, Fatemeh; N.M.Redzwan, F. (International Journal of Engineering and Technology, 2018)
In this paper, a study of analysis and design of cylindrical monopole plasma antenna for electrode-less discharge tube by using CST microwave studio is presented, as it has not been established yet. This analysis is very important which will be a basic concept of design a plasma antenna. A new design of cylindrical plasma antenna is investigated based upon the interaction of plasma elements due to the incident electromagnetic wave. The analysis for three types of gases (Argon, Neon and Hg-Ar) and different pressures are presented. It is shown that the different gases and different pressures will influenced the antenna performance.Â